Exploring A Sustainable Homestay: A Qualitative Study of Owner’s Participation - Pramanik, Purwanti Dyah; Maudiarti, Santi; Achmadi, Mochamad; Adriani, Hanni (Institut Pariwisata Trisakti, 2022)
Even though community participation was a crucial component of sustainable tourism, actual community participation was hard to achieve in developing countries. Only a few studies explored the local community participation in tourism villages. In response to this gap, this article explored owners’ participation to sustain their homestays. The research was built on descriptive and qualitative methods. The data were gathered by semi-structured interviews, participant observation, field notes, and photography. A sample population (6 persons) that include rural people and managers from a village. The result showed that cleanliness awareness was the homestay owners’ fundamental problem. The study also revealed that the homestay owners had not elaborated on their cultural uniqueness to create an unforgettable experience. They tried hard to design their homestays based on their knowledge rather than visitors’ demands. The external parties’ intervention, such as scholars, had to support the homestay owners to gain new insight into hospitality attitudes. Keywords: Community Involvement, Empowerment, Local Wisdom